Biomolecular Aspects of Schizophrenia - Patricia Wulandari (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2019)
Abstract Schizophrenia is a common psychiatric disorder, which is characterized by severe distortion of reality; disturbances in thoughts, feelings and behavior; according to DSM V is a disorder form deviations fundamentals and characteristics of thought and perception, and by the innapropriate or blunted affect. The influence of genetics is believed to have a role in psychiatric disorders, especially if the disorder has occurred in young adults or adolescents. The pathophysiology of schizophrenia is closely related to disorders of the biomolecular aspects of the central nervous system. Dopamine activity in the striatal area and prefrontal cortex is a mechanism believed to be the cause of the emergence of positive and negative symptoms in schizophrenia. Meanwhile, neuronal cell apoptosis and increased oxidants, especially in the basal ganglia and prefrontal cortex areas cause worsening of negative symptoms experienced by schizophrenic patients.